2018
DOI: 10.3168/jds.2017-13162
|View full text |Cite
|
Sign up to set email alerts
|

Transmission dynamics of intramammary infections caused by Corynebacterium species

Abstract: The development of reliable models for transmission of intramammary infections (IMI) is the subject of extensive research. Such models are useful to enhance the identification and understanding of factors that affect pathogen-specific IMI dynamics. Longitudinal transmission models are valuable for predicting infection outbreak risks, quantifying the effectiveness of response tactics, and performing response planning. In this work, we focused on modeling Corynebacterium spp. by using a compartmental model. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…has been frequently isolated from subclinical mastitis, our study highlights a positive correlation between this genus and clinical mastitis records. Using a longitudinal transmission model, Rachah et al 69 demonstrated an increase of new IMI caused by previous udder infections determined by Corynebacterium spp., which might explain the outbreaks of clinical mastitis.…”
Section: Resultsmentioning
confidence: 99%
“…has been frequently isolated from subclinical mastitis, our study highlights a positive correlation between this genus and clinical mastitis records. Using a longitudinal transmission model, Rachah et al 69 demonstrated an increase of new IMI caused by previous udder infections determined by Corynebacterium spp., which might explain the outbreaks of clinical mastitis.…”
Section: Resultsmentioning
confidence: 99%
“…The basic reproduction number R 0 is a combined value affected by the number of contacts per unit time, transmission probability per contact, and duration of the infectious period (Anderson and May, 1991). Dalen et al (2018) found that the cure rate for subclinical IMI differed significantly between 2 farms with the same mastitis pathogen, and that this difference affected the prediction of transmission dynamics of the same pathogen in each farm. With herd-specific knowledge of which transmission parameters have most effect on transmission dynamics, we can improve udder health management by focusing preventive actions on those management areas that are related to the transmission parameters of concern for each specific herd.…”
Section: Discussionmentioning
confidence: 98%
“…Poisson regression is a commonly applied method for estimating transmission rates in both epidemic and endemic scenarios ( 8 , 19 ). We here wanted to assess and compare the transmission rates of Corynebacterium spp.…”
Section: Methodsmentioning
confidence: 99%
“…We used the term log( S int · I int / N int ) as an offset in the regression analysis, meaning that this model reflects contagious transmission directly between cows. Like in Dalen et al ( 8 ), we also constructed a similar model with log( S int ) as the offset, they mimic a fixed rate of infection, independent of the proportion of infected animals present at the sampling points. This model reflects environmental transmission where pathogens come from a reservoir in the environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation